MANAGEMENT CASE OF POST PHAKIC INTRAOCULAR LENS IMPLANT IN HIGH MYOPIA WITH COMPLICATED CATARACT AFTER VITRECTOMY: POST SURGERY CHALLENGES - Syska Widyawati; Herdanti Rahma Putri; Virna Dwi Oktarina (International Journal of Retina, 2022)
Introduction: To highlight the therapeutic dilemma in managing complications in high myopia patient with complicated cataract after vitrectomy who previously had refractive surgery. Case Report: A 37-years old man, presented with half the right eye view was being blocked by a black curtain for one week before admission. He had a history of high myopia on both eyes and underwent phakic intraocular lens (PIOL) implantation 12 years ago. Presenting visual acuity (VA) of the right eye was hand motion (HM). Retinal detachment (RD) on inferior side, and clear lens with anterior chamber (AC) PIOL were found in the examination. Patient underwent vitrectomy, endolaser, and silicone oil in the next four days. A sudden severe pain with red-eye was found one month after surgery, intraocular pressure (IOP) was increased to 43 mmHg, the lens was white opaque with lens material seen in AC. Discussion: The diagnosis of traumatic cataract and lens-particle-induced glaucoma was made. Lens mass evacuation surgery was performed after initial antiglaucoma medication. Posterior capsule rupture was found intraoperatively with only a small amount of lens mass remaining. Visual acuity result after the second surgery is still dissatisfied with the presence of rubeosis iridis, with the possibility of retinal re-detachment was still present. Conclusion: High myopia still poses a greater risk of ocular complications. It can be corrected by refractive surgery, with expensive cost and it will not prevent potential future ocular problems. Repeated assessment before and after refractive surgery procedure is mandatory in order to prevent sight-threatening complications of high myopia which might lead to other blinding complications.